2021
DOI: 10.3390/cancers13174492
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metastasis-Related microRNAs in Prostate Cancer Progression and Treatment

Abstract: Prostate cancer (PCa) is one of the most prevalent cancer types in males and the consequences of its distant metastatic deposits are the leading cause of PCa mortality. Therefore, identifying the causes and molecular mechanisms of hematogenous metastasis formation is of considerable clinical importance for the future development of improved therapeutic approaches. MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression at the post-transcriptional level by targeting messenger RNAs. Numerous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 125 publications
0
30
0
Order By: Relevance
“…Some therapies that work against the consequences of altered genes (e.g., use of olaparib for HRR gene-mutated metastatic castrationresistant prostate cancer [70,71]) were already granted FDA approval (all FDA-approved therapies for PCa are listed in Reference [72] and partially discussed in Reference [73]). Gene therapy targets not only protein-coding genes but also long non-coding RNAs [74] and microRNAs [75]. PCa FDA-approved therapies also include inhibitors of the androgen receptor signaling, such as enzalutamide [76,77] and darolutamide [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Some therapies that work against the consequences of altered genes (e.g., use of olaparib for HRR gene-mutated metastatic castrationresistant prostate cancer [70,71]) were already granted FDA approval (all FDA-approved therapies for PCa are listed in Reference [72] and partially discussed in Reference [73]). Gene therapy targets not only protein-coding genes but also long non-coding RNAs [74] and microRNAs [75]. PCa FDA-approved therapies also include inhibitors of the androgen receptor signaling, such as enzalutamide [76,77] and darolutamide [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 exosomes can be quantitatively labeled using PD-L1 antibody-modified Au@Ag@ MBA-SERS labeling. Mi RNA plays an important role in the post-transcriptional regulation of gene expression and plays an essential role in the diagnosis and treatment of tumors ( Li et al, 2021a ; Andrikopoulou et al, 2021 ; Crudele et al, 2021 ; Konoshenko et al, 2021 ; Oh-Hohenhorst and Lange, 2021 ). The nature of the exosomal lipid bilayer avoids miRNA degradation, making the specific miRNAs in exosomes well suited as biomarkers for early cancer diagnosis and prognosis.…”
Section: Sers Technology For Exosome Detectionmentioning
confidence: 99%
“…Due to a multitude of treatment options that often offer curative potential, localized disease generally portends favorable outcomes, with 5-year survival for localized and regional disease being nearly 100% (17). However, despite noteworthy recent progress in therapeutic measures, metastatic prostate cancer still inflicts significant morbidity and mortality, with the preponderance of fatal cases of prostate cancer attributed to metastatic burden (18)(19)(20).…”
Section: Cancermentioning
confidence: 99%
“…Whereas some of these metastasis-promoting miRNAs directly activate oncogenic pathways via known proto-oncogenes, others silence or suppress tumor-suppressive pathways to promote prostate cancer metastasis. For example, Ren et al demonstrated that miR-210-3p sustains the activation of nuclear factor kappa -B (NF-κB) signaling by targeting tumor necrosis factor-α (TNFα), which increases the capacity for cellular invasion, migration, EMT, and formation of bone metastases (19,30). On the other hand, Yu et al…”
Section: Metastasis-promoting Mirnas In Prostate Cancermentioning
confidence: 99%